Topochemical synthesis of novel electronic materials - Denis Romero, F (2014)
units separated by rock salt SrCl layers. Variable-temperature diffraction measurements reveal that these sheets undergo a cooperative Jahn-Teller distortion at T ~ 200 K due to unevenly filled degenerate (dxy, dyz) orbitals. This material adopts a magnetic structure in which the moments within each sheet are ordered antiferromagnetically, but the sheets are aligned ferromagnetically. An investigation was carried on the reduction behaviour of Ru-doped Sr(RuxFe1-x)O3. It was found that the reduction was non-topochemical for values of x > 0.5. For values of 0 < x < 0.5, no single phase precursor material could be formed. For the material with x = 0.5, reduction with CaH2 produced a new phase with composition Sr(Ru0.5Fe0.5)O2. This material is the first reported instance of Ru2+ in an extended transition metal oxide. DFT calculations reveal that, while the iron centres adopt a high-spin configuration, the ruthenium centres are in an intermediate-spin S = 1 configuration. Resulting competing magnetic interactions lead to frustration and lack of ordering. In order to further study the reduction behaviour of extended transition metal oxides containing ruthenium, the reduction of Sr2(Ru0.5Fe0.5)O4 and Sr3(Ru0.5Fe0.5)2O7 was performed using CaH2 as a solid state reducing agent. In these cases, reduction leads to segregation of the materials into multiple phases adopting closely related structures that differ mainly in their oxygen content. In these materials, the ruthenium centres are preferentially reduced, such that starting from materials containing Ru5+ and Fe3+, materials containing Ru(3-7 δ)+ and Fe3+ are produced. Similarly, the low-temperature oxidation using CuF2 as a solid state fluoride source was performed on materials with composition Sr3(Ru0.5M0.5)2O7 (M = Ti, Mn, Fe). In the case of M = Mn and Ti, materials with composition Sr3(Ru0.5Fe0.5)2O7F2 are produced in which the ruthenium centres are oxidised to Ru6+. For the M = Fe material, oxidation results in partial exchange of O for F and a material with composition Sr3(Ru0.5Fe0.5)2O5.5F3.5 in which the ruthenium centres are oxidised from +5 to +5.5 while the iron centres remain in a +3 oxidation state. While fluorination of the M = Ti leads to increasing itinerant electronic behaviour, fluorination of the M = Mn and Fe materials induces a twisting of the MX6 octahedra that enables magnetic order to emerge at low temperatures. Finally, reaction of the SrO(SrVO3)n (n = 1, 2, ∞) series of phases with CaH2 results in the formation of phases with composition SrO(SrVO2H)n (n = 1, 2, ∞), the first examples of stoichiometric oxyhydride materials. SrVO2H is magnetically ordered at room temperature, while the n = 1 and n = 2 materials order at 170 K and 240 K respectively. The high magnetic ordering temperature arises from strong interactions between (dxy, dyz) orbitals in a manner analogous to the reduced iron-containing phases SrO(SrFeO2)n.